Analisis Kesadaran Pengusaha UMKM Dalam Kepemilikan NPWP Pada Pengusaha UMKM Pasar Km 5 Kota Palembang - Novryzal Novryzal; Yuhanis Ladewi; Saekarini Yuliachtri (Politeknik Negeri Sriwijaya, 2020)
The formulation in this study is how the level of awareness of MSME entrepreneurs in KM S Market in the obligation to have a Taxpayer Identification Number The goal is to determine the level of awareness of MSME entrepreneurs in KM 5 Market in the obligation to have a Taxpayer Identification Number. This rescarch is a descriptive research The population used in this study were 123 SMES in the km 5 market of Palembang city. The sample in this study were 55 respondents. The data collection methods used in this study were interviews and questionnaires The data analysis used in this research is qualitative analysis. The results of this study indicate that the awareness of ownership of a Taxpayer Identification Number (NPWP) in the Micro, Small and Medium Enterprises (Umkm) Pasar Km 5 Palembang City as sources and respondents in this study is still lacking due to a lack of knowledge of taxation and the economic level that is still low. low and lack of socialization provided by the government.